PHYTOCHEMICAL ANALYSIS OF PETROLEUM ETHER EXTRACT OF GRATELOUPIA FILICINA (LAMOUROUX) C.AG. USING FTIR AND HPLC (International Journal of Food and Nutritional Sciences, 2022)
Marine algae are a source of bioactive substances and they produce a great variety of secondary metabolites with a diverse range of biological activities. Phytochemical types include sterols, isopyrenoids, amino acids, terpenoids, phlorotannins, steroids, phenolic compounds, halogenated ketones and alkanes, cyclic polysulphides, fatty acids and acrylic acid have been isolated from marine algae. Hence, pharmacologists, physiologists and chemists have been paying increasing attention to the marine organisms particularly on marine macro algae for screening bioactive substances. The present study was designed to discover the phytochemical analysis of petroleum ether extract of Grateloupia filicina (Lamouroux) C.Ag. collected from Manapad, Thoothukudi district, Tamil Nadu, India. The phytochemical screening of petroleum ether extract was carried out by using the standard procedure of FTIR spectroscopy and HPLC. The FTIR spectrum of the petroleum ether extract of Grateloupia filicina (Lamouroux) C.Ag. was revealed the presence of functional groups such as Aliphatic amines, Nitro compounds, Aromatics, Alkenes, Aldehydes, Esters, Alkanes and Carboxylic acids. The qualitative HPLC fingerprint profile displayed three compounds at different retention times of 1.293 min, 2.287min and 2.750 min indicate the presence of three compounds. The profile displayed the most prominent peak of maximum area percentage (93.4%) with the retention time of 2.287 min. The phytochemicals were characterized which showed the presence of secondary metabolites. The results of this study provide a base work for utilizing petroleum ether extract of Grateloupia filicina (Lamouroux) C.Ag., as a treatment for a variety of disorders.